Analysis of risk factors behind keloid - Manoharan, Anbumalar; Rao, Sowmya Manasa (International Journal of Research in Dermatology, 2020)
Background: Keloids are firm, thickened, bosselated tumors with fibrous tissue which expands beyond the original injury with common sites being presternum, shoulder, ear lobes. They are more common in Blacks and Hispanics than Caucasians. As there is paucity of studies from South India, this study is done to identify the epidemiological features and analyse the risk factors involved in keloid formation and compare it with previous studies. Methods: 60 subjects were included in the study. Keloid was diagnosed clinically and factors such as the age at presentation, gender, site, size, duration, number and predisposing factors to keloid formation were assessed among them for a period of 18 months. Results: Most of the patients were in the age group of 20-40 years and maximum were females. Majority of patients around 51.67% were affected in chest followed by shoulder (20%). In our study 61.67% patients had keloids of size ≤5 cm and 23 (38.33%) patients had size >5 cm. Most of the patients (41.67%) had keloids of <2 years duration. Maximum number of the patients (68%) had single keloid. 50% of the patients had keloids which occurred after trauma followed by acne (15%), surgery (10%) and herpes zoster (10%), burns (5%). 10% of the patients had spontaneous onset of keloids. Conclusions: The epidemiological features found in this study were similar to the studies conducted in the different parts of the world. Elimination of exacerbating factors will prevent further keloid formation thereby playing a crucial role in the management.